(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The concept of emotional intelligence is of unparalleled interest in both the popular literature and within academia. Much work is being done to discover exactly what emotional intelligence encompasses and how it would be most effectively applied. The present paper will attempt to review the literature surrounding emotional intelligence (E.I.). It shall study the construct of E.I. by reviewing the different models, the measures used to assess them, and the relationship between these models and other similar constructs. Further, it will review the applicability of the E.I. construct to applied academic settings and shall propose how future research in this area could be applied to various levels to enhance teacher effectiveness.